Forward modeling and interpretation of resistivity and IP profiles in Central Skellefte District, Northern Sweden - Derrien, Morvan (2010)
A 2D-resistivity/IP survey was conducted in Central Skellefte District (CSD) along two profile lines (Northern profile and Southern profile). The presented work aims to get a better idea of the subsurface resistivity, and to improve the understanding of the geology, by creating a 3D-forward model of the area and comparing it with the field data. It can also help to constrain the results of the inversion of the field data for this area. The forward modeling was created with Res3DMod software, supported by laboratory resistivity measurements of representative samples and on the bedrock map of the Central Skellefte District. After inversion of the forward model data and the field data using Res2DInv software, forward model profiles and field data profiles were compared. The field profiles allow to differentiate the geological units of the CSD, i.e. the metavolcanic series of the Skellefte Group and the overlying metasediments of the Vargfors Group. The forward model shows that the geometries displayed on the field profile are not necessarily representative of the real geological structures, and that the pseudodepths could sometimes lead to some errors. It also shows that some anomalies are artifacts due to inversion process. Validerat; 20101217 (root)